Impact of urbanization on customary land tenure : a case study of Baruni Village, Port Moresby, Papua New Guinea - Mero, Christopher Siaoa; Goede, J.H. de; Kaji, Hideki; Dias, Hiran D.; Government of Australia (Bangkok : Asian Institute of Technology, 1979)
The most obvious fact about urban development is that it occupies and uses land. Both the supply of land and its location are mostly fixed; using land for a particular purpose will necessarily have an impact on its avail ability for other uses. Therefore, allocation of land is a conflicting issue of urban development. Consequences arise between short-term needs and the long term consequences that drive from l and tenure practices. Different socio-economic needs and functions compete for the same land space. Individual and private needs may come into collision with collective land use requirements, and local, regional and national interests may conflict over the use of land. The essential aim of urban land policy is to provide the l and needed in the right place, at the right time and at low cost. This aim cannot be achieved solely through compulsory acquisition. Nor will a more active role by the public authorities in the form of advanced l and acquisition automatically solve all the problems of future development without careful planning and fair acquisition. Also, local , regional and national interests will continue to be in conflict. Even where private ownership of land has been eliminated, public agencies with various functions may have their own vested interests. Adequate legislation, planning and fair acquisition, can, however, create the framework for an urban land policy that is more efficient and more responsive to the needs of society than present methods of allocation. The people who own the land are the key to the problem. Never neglect them. A development tool that is creative is necessary. Participation of land owners is fundamental for land acquisition and development .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1979
Keywords: Urbanization -- Papua New Guinea -- Port Moresby